2023
DOI: 10.1111/imr.13301
|View full text |Cite
|
Sign up to set email alerts
|

Decoding immunogenic cell death from a dendritic cell perspective

Sophie Janssens,
Sofie Rennen,
Patrizia Agostinis

Abstract: SummaryDendritic cells (DCs) are myeloid cells bridging the innate and adaptive immune system. By cross‐presenting tumor‐associated antigens (TAAs) liberated upon spontaneous or therapy‐induced tumor cell death to T cells, DCs occupy a pivotal position in the cancer immunity cycle. Over the last decades, the mechanisms linking cancer cell death to DC maturation, have been the focus of intense research. Growing evidence supports the concept that the mere transfer of TAAs during the process of cell death is insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 251 publications
0
2
0
Order By: Relevance
“…Previous studies found that more severe ER stress can lead to higher ICD ( 25 , 26 ). Direct ROS-based ER stress is more effective for induction of ICD than is secondary collateral ER stress.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies found that more severe ER stress can lead to higher ICD ( 25 , 26 ). Direct ROS-based ER stress is more effective for induction of ICD than is secondary collateral ER stress.…”
Section: Discussionmentioning
confidence: 91%
“…Immunotherapy, especially immune checkpoint blockade (ICB), has been a breakthrough in cancer treatment in recent years. However, its clinical efficacy is often limited by T-cell deprivation and poor immunogenicity in solid tumors. Many efforts have been made to turn “immune-cold” to “immune-hot” tumors to potentiate immunotherapy. , Among them, chemotherapy can induce immunogenic cell death (ICD) to reinforce tumor immunogenicity while killing tumor cells, thus showing great potential to synergize with ICB . During ICD, the dying tumor cells can release damage-associated molecular patterns (DAMPs) to stimulate dendritic cells (DCs) maturation and further facilitate effector T-cell infiltration. However, the high expression of redox substances in the tumor microenvironment (TME) causes abnormal redox homeostasis, which restricts the chemotherapy-induced ICD effect . Thus, destroying redox homeostasis in the TME is necessary for amplifying chemotherapy-sensitized ICB therapy.…”
mentioning
confidence: 99%